The Hope for Gains and the Reality of Loss - Encarnacion Tadem, Teresa S. (Kasarinlan: Philippine Journal of Third World Studies, 2011)
In 2005, the Third World Studies Center (TWSC) launched a policy dialogue series on “The Decade-Long Membership of the Philippines in the World Trade Organization (WTO).” This five-part lecture series generated issues, concerns, and debates among members of the academe, nongovernmental organizations as well as government functionaries on the costs of benefits of the country’s membership in the WTO. Topics covered ranged from the gains, losses, and prospects of the country on the Agreement on Agriculture (AoA), its commitments to the General Agreement on Trade and Services (GATS) and Intellectual Property Rights (IPR), and the country’s negotiating strategy in the 2005 WTO Ministerial Meeting in Hong Kong.